Glutamate concentration in the anterior cingulate cortex in alcohol dependence: association with alcohol withdrawal and exploration of contribution from glutamatergic candidate genes. (October 2018) - Streit, Fabian; Treutlein, Jens; Frischknecht, Ulrich; Hermann, Derik; Mann, Karl; Kiefer, Falk; Sack, Markus; Hall, Alisha S.M.; Frank, Josef; Witt, Stephanie H.; Foo, Jerome C.; Degenhardt, Franziska; et al.
Abstract : Supplemental Digital Content is available in the text.